Espresso tales - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- 44 Scotland Street series, 2006)
Espresso Tales features further escapades from the fringes of the New Town which appeared in The Scotsman during 2005. This new novel gives Scotland Street aficionados a chance to catch up with the occupants of what must surely be Edinburgh's most well-known literary address, and to meet more of the inhabitants of this unique corner of the city. Espresso Tales is vintage McCall Smith, tackling issues of trust and honesty, snobbery and hypocrisy, love and loss, but all with great lightness of touch. Clever, elegant and funny, this is a novel that provides huge entertainment but which is underpinned by the moral dilemmas of everyday life and the characters' struggles to resolve them.